Improvement in wettability of porous Si by carboxylate termination. (18th January 2018) - Sakakibara, Masanori; Matsumoto, Kimihisa; Kamiya, Kazuhide; Kawabata, Shigeki; Inada, Mitsuru; Suzuki, Shinya
Abstract: The effects of the surface terminations of carboxylic acid and carboxylate on the hydrophilicity of porous Si were studied to observe the changes in the photoluminescence (PL) intensity of water-dispersed porous Si powder over time. Porous Si terminated by carboxylate was produced from carboxylic acid-terminated porous Si by a neutralization reaction with an alkali metal. After the neutralization of porous Si terminated by carboxylic acid, the formation of carboxylate-terminated porous Si was confirmed by observing the absorption peaks corresponding to Si–C and COO − from Fourier transform infrared (FT-IR) spectra. On the basis of changes in the PL intensity of porous Si over time, the hydrophilicity of porous Si terminated by carboxylate was determined to be higher than that of porous Si terminated by carboxylic acid. On the other hand, nonradiative recombination centers on the surface of carboxylate-terminated porous Si were formed during the neutralization process, which reduced the PL intensity. The PL from porous Si terminated by carboxylic acid and carboxylate was caused by the quantum size effect regardless of the termination molecules, which was confirmed by the wavelength dependence of the PL lifetime. Porous Si terminated by undecylenate is an effective material for applications such as bio-labels owing to its hydrophilicity and high PL stability.